Semantic Integration of Sensor Data and Disaster Management Systems: The Emergency Archetype Approach. (7th May 2013) - Lezcano, Leonardo; Santos, Leopoldo; García-Barriocanal, Elena
The Semantic Sensor Web (SSW) allows emergency response management (ERM) systems to consume sensor data and improve response time and effectiveness. It is also a fact that ERM must be carried out as a multiorganizational task to combine sensor data with human decisions and observations. A frequent problem in such scenarios is that current formats for data exchange do not support sensor data in a way that allows semantic interoperability between heterogeneous ERM systems. Therefore, part of the semantic richness coming from the SSW, such as the Semantic Sensor Network Ontology (SSNO), is lost when sensor data is embedded in current ERM messages. To bridge the gap, an application of the two-level paradigm to the ERM domain is proposed. The advantages of using "emergency archetypes" include semantic data integration and flexibility to represent new types of messages, without losing the support for seamless exchange between heterogeneous ERM systems. Emergency archetypes can reuse the terminologies and ontologies available in the ERM domain so that systems based on previous formats can switch to archetypes in a straightforward process. Finally, a method to attach rules to emergency archetypes is explained, allowing not only the semantic interoperability of ERM data but also of the inference knowledge that trigger alerts and support decision making.